Evaluation of the self-reported questionnaires used to assess mental health after the January 2015 terrorist attacks in the Paris Region: IMPACTS survey - L. Bertuzzi; C. Vuillermoz; T. El Aarbaoui; M. Héron; L. Aubert; P. Pirard; S. Vandentorren; Y. Motreff (European Psychiatry, 2022)
Introduction Structured clinical interviews are the gold standard for assessing mental health. However limited resources may allow the use of only self-report questionnaires. In the context of emergency, such as terrorist attacks, the performance and thresholds of such tools still unclear.